Pembuatan dan Pelatihan Pengelolaan Website SD Negeri 2 Majangtengah Sebagai Media Informasi dan Promosi - Irawan, Paulus Lucky Tirma; Rahmadianto, Sultan Arif (Alamtana: Jurnal Pengabdian Masyarakat UNW Mataram, 2025)
SD Negeri 2 Majangtengah is a public elementary school located in Dampit Sub-district, Malang Regency. This institution serves as one of the target schools for the Merdeka Belajar Kampus Merdeka (MBKM) Teaching Campus program. The Teaching Campus program is designed to introduce educational change agents, particularly in 3T regions (frontier, remote, and underdeveloped areas), to enhance literacy and numeracy proficiency as well as technology adaptation. Based on observations conducted during the role as Field Supervising Lecturer (DPL), SD Negeri 2 Majangtengah faces several challenges, including the absence of appropriate media for school data management. The institution's infrastructure data and student academic records are still managed conventionally using physical books. This type of management system is susceptible to damage and inconsistencies, rendering it insufficiently reliable for long-term use. The limited level of technology adaptation is suspected to be one of the contributing factors to the low literacy and numeracy levels among students. In this community service activity, a website-based profile media has been designed and developed using a User Centered Design (UCD) approach. This profile website functions as a medium for school information and communication, a platform for exhibiting academic achievements of students and teachers, a limited-scale teaching medium, and a supporting medium for the school's digital branding to the broader public. Black box testing results demonstrate that all application features operate effectively. Meanwhile, SUS Scoring measurements of 72.37 (grade B) indicate that the application possesses good design quality.